2008
DOI: 10.1037/0278-6133.27.3.388
|View full text |Cite
|
Sign up to set email alerts
|

The need for integrating behavioral care in a college health center.

Abstract: The findings suggest that increased awareness of behavioral problems influences treatment-decision making at a university health service, and therefore this setting would be fertile ground for implementation of an integrated care model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(17 citation statements)
references
References 15 publications
(10 reference statements)
1
16
0
Order By: Relevance
“…Many students who present at college health centers have mental health problems [103]. Thus, a collaborative relationship between university health centers and behavioral health services may lead to an increase in identification and referrals for behavioral health treatments of students with mental health problems.…”
Section: Significance Of Early Identification Of Mental Health Problementioning
confidence: 99%
“…Many students who present at college health centers have mental health problems [103]. Thus, a collaborative relationship between university health centers and behavioral health services may lead to an increase in identification and referrals for behavioral health treatments of students with mental health problems.…”
Section: Significance Of Early Identification Of Mental Health Problementioning
confidence: 99%
“…Based on the lack of findings related to integrated services, the current data do not support recent arguments that UCCs should provide additional services beyond counseling. It has been suggested that an overhaul of university healthcare and the integration of behavioral and medical care would greatly improve the detection and treatment of mental health problems, save costs, and improve other outcomes (e.g., dropping out of college; Alschuler et al, 2008). The current study's findings would not support doing so, and therefore decisions about supplemental services should be determined based on self-study at the UCC.…”
Section: Practice and Advocacy Implicationsmentioning
confidence: 63%
“…Additionally, college counseling center staff could provide basic counseling skills and crisis assessment trainings to university health center staff to increase ease/competence in these conversations. Widespread depression screening with the PHQ-9, as recommended by Klein and colleagues (2011), has potential to facilitate depression detection in primary care settings and support subsequent referral of students to college counseling centers (Alschuler et al, 2008;O'Connor, Whitlock, Beil, & Gaynes, 2009). Additionally, increased opportunities for consultation among college counseling staff and health center/primary care providers could help highlight the importance of depression screening for all patients and appropriate follow-up with depressed patients.…”
Section: Discussionmentioning
confidence: 96%
“…Mental health screening among college health center patients is associated with increased mental health treatment (Alschuler, Hoodin, & Byrd, 2008). However, the frequency of use of depression screening inventories in collegebased primary care settings is unknown.…”
mentioning
confidence: 97%